TiCN composite coating and preparation method thereof

By depositing Ti transition layer, TiN intermediate layer and TiCN surface layer in sequence on the substrate surface, and preparing TiCN composite coatings using high power pulse magnetron sputtering technology, the problems of high friction coefficient and low bond strength of existing TiCN coatings are solved, lower friction coefficient and higher bond strength are achieved, and the service life of cutting tools and molds is extended.

CN119800281APending Publication Date: 2025-04-11LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411957658.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing TiCN coating has a high friction coefficient and low bond strength, which leads to the coating being easily peeled off and cannot fully exert lubricating performance, limiting the service life of cutting tools and molds.

Method used

The TiCN composite coating is prepared by high-power pulsed magnetron sputtering technology. By depositing Ti transition layer, TiN intermediate layer and TiCN surface layer in sequence on the substrate surface, the percentage of element atoms and process parameters are regulated to improve the hardness and bonding strength of the coating.

Benefits of technology

The friction coefficient of the TiCN composite coating is significantly reduced, the bonding strength between the coating and the substrate is improved, and the lubricating performance is enhanced, thereby extending the service life of cutting tools and molds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800281A_ABST
    Figure CN119800281A_ABST
Patent Text Reader

Abstract

The invention provides a TiCN composite coating and a preparation method thereof, and relates to the technical field of coating lubrication, the TiCN composite coating comprises three layers, the bottom layer is a Ti coating, the middle layer is a TiN coating, the surface layer is a TiCN coating, the TiCN composite coating comprises 20-30 at.% of N, 15-30 at.% of Ti and 40-65 at.% of C, the thickness is 710-1030 nm, a high-power pulse magnetron sputtering technology is adopted, Ti transition layers are sequentially deposited on the surface of a base body, and a TiCN transition layer is formed on the surface of the base body. The coating comprises a TiN coating and a TiCN coating. The TiCN coating has the advantages that the friction coefficient of the TiCN coating is improved, the hardness of the coating and the bonding strength of the coating and a matrix are improved, the frictional wear of a cutting tool is reduced, the working stability is improved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a TiCN composite coating and a preparation method thereof, and relates to the technical field of coating lubrication. Background Art

[0002] TiCN coating has been studied as a reliable hard film coating material. Due to its high hardness, toughness, low friction coefficient and excellent wear resistance, it is widely used in cutting tools, molds and other fields. With the development of modern industry, higher requirements are put forward for cutting tools and molds. In order to better improve their service life, in addition to excellent mechanical properties, they also need to have good tribological properties to achieve wear resistance and friction reduction. At present, a single binary coating such as TiN coating has been difficult to meet the increasingly stringent working conditions. Although TiC has a high hardness, it has low bonding strength, and the bonding force between the coating and the substrate is insufficient, which can easily cause the coating to peel off and fail. TiCN coating is a solid solution of TiN coating and TiC coating, combining the advantages and characteristics of both. TiCN coating has better friction behavior and high thermal conductivity, which can improve the lubrication performance of the coating and reduce the friction coefficient. However, with the continuous improvement of the performance requirements for cutting parts, the use conditions of the coating have become more and more stringent, which puts higher requirements on the reliability and service life of the protective coating. At present, there are few studies on TiCN prepared by high-power pulsed magnetron sputtering technology, and the friction coefficient of TiCN coating prepared by PVD technology is high, and the lubrication performance needs to be further strengthened, which cannot further reduce the wear of cutting parts and increase the life of cutting parts. In addition, the bonding strength between TiCN coating and substrate is low, which easily leads to coating peeling failure, limiting the service life of coating, and failing to give full play to the lubrication performance of coating, increasing the wear between cutting tools, and reducing the life of cutting parts. Summary of the invention

[0003] The invention provides a TiCN composite coating and a preparation method thereof, which solves the technical problems of high friction coefficient and low bonding strength of the TiCN coating in the prior art.

[0004] The present invention is implemented as follows: the bottom layer is a Ti coating, the middle layer is a TiN coating, and the surface layer is a TiCN coating. The elements and their atomic percentages in the TiCN composite coating are N 20-30at.%, Ti 15-30at.%, and C 40-65at.%. Too high a C element content may cause the hardness of the coating to be too low, and too low a C element content may cause the friction coefficient of the coating to be too high and the lubrication performance to be poor. In addition to ensuring that the coating has good hardness, an appropriate C element content also has the effect of reducing the friction coefficient.

[0005] As a further preference, the total thickness of the TiCN composite coating is 710-1030 nm, the thickness of the bottom layer is 90-100 nm, and the thickness of the middle layer is 70-80 nm.

[0006] The preparation method of the TiCN coating adopts high-power pulsed magnetron sputtering technology to sequentially deposit a Ti transition layer, a TiN coating and a TiCN coating on the surface of a substrate.

[0007] As a further preference, the process conditions for depositing the Ti transition layer are: argon flow rate 60sccm, substrate bias -200V, frequency 80kHz, pulse width 6μs, a high-power pulse power supply is added to the pure Ti target, the peak current is adjusted to 180A, the frequency is 100Hz, the pulse width is 500μs, the average output power is 5kW, and the deposition time is 15min.

[0008] As a further preference, the process conditions for depositing the TiN coating are: Ti target peak current 180A, frequency 100Hz, pulse width 500μs, average output power 5kW, argon flow rate 60sccm, and nitrogen is introduced and the flow rate is continuously adjusted to 8-30sccm, bias voltage -150V~-180V, frequency 80kHz, pulse width 6μs, and deposition 10min.

[0009] As a further preference, the process conditions for depositing the TiCN coating are as follows: Ti target peak current 180A, frequency 100Hz, pulse width 500μs, average output power 5kW, argon flow rate 60sccm, nitrogen flow rate 30sccm, bias voltage -120V, and acetylene is gradually introduced at 8-10sccm. After deposition for 5min, the bias voltage is adjusted to -90V, the acetylene flow rate is maintained at 10sccm, the argon flow rate is adjusted to 30-90sccm, and the deposition time is 120min.

[0010] As a further preference, the substrate is pre-treated and pre-sputtered and cleaned before the coating is deposited.

[0011] As a further preference, the pretreatment step includes: ultrasonic cleaning with anhydrous ethanol and petroleum ether for 30 minutes respectively, and placing in a drying chamber after drying.

[0012] As a further preferred embodiment, the pre-sputtering cleaning step includes: placing the pre-treated substrate into a vacuum chamber for evacuation, wherein the vacuum degree is less than 1×10 -3 Pa, start ion etching on the substrate surface, introduce argon gas with a flow rate of 350sccm, apply a pulse bias on the substrate, the bias is -850V, the frequency is 40kHz, the pulse width is 4μs, the etching pressure is 1.1Pa, and pre-sputter clean the substrate with argon plasma for 20min.

[0013] As a further preference, the substrate is made of steel.

[0014] The invention has the beneficial effects that the high-power pulsed magnetron sputtering technology has the advantage of a higher metal ionization rate, and the coating process parameters are regulated to obtain the optimal deposition parameters. By constructing an intermediate transition layer TiN, the interface physical property mutation is reduced, and the hardness of the coating and the bonding strength between the coating and the substrate are improved. The TiCN composite coating of the invention has a simple preparation process, not only has a higher film-base bonding force, but also has a lower friction coefficient, and exhibits excellent lubricity. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 is a cross-sectional SEM image of the TiCN composite coating prepared in Example 1;

[0017] Figure 2 is a bonding force diagram of the TiCN composite coating prepared in Example 1;

[0018] Figure 3 is a light microscopy result image of the scratch of the TiCN composite coating prepared in Example 1;

[0019] Figure 4 This is a friction coefficient curve of the TiCN composite coating prepared in Example 1. DETAILED DESCRIPTION

[0020] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings, and the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] A TiCN composite coating with high film-base bonding strength and low friction coefficient is prepared by high-power pulsed magnetron sputtering technology. The specific preparation steps are as follows:

[0023] (1) Pretreatment

[0024] The 9Cr18 alloy steel block substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 minutes respectively, and then placed in a drying chamber for standby use after being blown dry.

[0025] (2) Pre-sputtering cleaning

[0026] The 9Cr18 alloy steel block sample treated in step (1) is placed in a vacuum chamber for evacuation. When the vacuum degree is lower than 1×10-3Pa, ion etching of the substrate surface is started. Argon gas is introduced at a flow rate of 350sccm. A pulse bias voltage of -850V, a frequency of 40kHz, a pulse width of 4μs, and an etching pressure of 1.1Pa is applied to the steel block sample. The steel block sample is pre-sputtered and cleaned for 20min using argon plasma.

[0027] (3) Deposition of Ti transition layer

[0028] High-power pulse magnetron sputtering technology was used, the argon flow rate was adjusted to 60sccm, the substrate bias was continuously adjusted to -200V, the frequency was 80kHz, and the pulse width was 6μs. A high-power pulse power supply was added to the pure Ti target, the peak current was adjusted to 180A, the frequency was 100Hz, the pulse width was 500μs, the average output power was 5kW, and a 90-100nm Ti transition layer was deposited for 15min.

[0029] (4) Deposition of TiN coating

[0030] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the argon flow rate was unchanged, nitrogen with a flow rate of 8 to 30 sccm was introduced, a pulse bias was applied to the steel block sample, the bias was -150 V, the frequency was 80 kHz, the pulse width was 6 μs, the deposition time was 10 min, and a TiN coating with a deposition thickness of 70 to 80 nm was formed.

[0031] (5) Deposition of TiCN coating

[0032] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept constant, the frequency was 100 Hz, the pulse width was 500 μs, the average output power was 5 kW, and the argon flow rate was kept constant at 60 sccm and the nitrogen flow rate was kept constant at 30 sccm. Acetylene was introduced, and the acetylene flow rate was continuously adjusted to 8-10 sccm. The bias voltage was adjusted to -120 V for deposition for 5 minutes. Then, the acetylene flow rate was kept at 10 sccm, the bias voltage was continuously adjusted to -90 V, the argon flow rate was adjusted to 30 sccm, and the deposition time was 7200 s to deposit the TiCN coating.

[0033] Example 1 is a best implementation example. The elements and their atomic percentages in the TiCN composite coating are N 25 at.%, C 55 at.%, and Ti 20 at.%. Figure 1The thickness of the TiCN composite coating prepared in Example 1 is 710 nm, wherein the thickness of the bottom layer is 90-100 nm and the thickness of the middle layer is 70-80 nm. Figure 2 The scratch test was conducted using a multifunctional material surface performance tester (MFT-4000). The equipment has a 120° cone angle HRC-3 and a diamond Rockwell indenter with a tip radius of 0.2mm. The end load was set to 90N, the scratch length was 5mm, and the loading speed was 50N / min. The scratch test was conducted and the friction coefficient, friction force curve, and loading force curve were obtained. The scratch morphology of the coating was observed using an optical microscope (NMM-800) with a magnification of 100 times. The comprehensive judgment was that the bonding force of the coating was 48N. Figure 3 , the scratch morphology observed by a 100x microscope equipped with a multifunctional material surface performance tester. When the coating is scratched and severely peeled off and leaks out of the substrate, it is judged that the coating has failed. The coating is scratched and the substrate is exposed when the loading force is 48N. Figure 4 The coating was subjected to a reciprocating friction test using a CSM friction tester in an atmospheric environment using a 9Cr18 steel ball with a diameter of 6 mm. The average friction coefficient measured was approximately 0.21.

[0034] Example 2

[0035] A TiCN composite coating with high film-base bonding strength and low friction coefficient is prepared by high-power pulsed magnetron sputtering technology. The specific preparation steps are as follows:

[0036] (1) Pretreatment

[0037] The 9Cr18 alloy steel block substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 minutes respectively, and then placed in a drying chamber for standby use after being blown dry.

[0038] (2) Pre-sputtering cleaning

[0039] The 9Cr18 alloy steel block sample treated in step (1) is placed in a vacuum chamber for evacuation. When the vacuum degree is lower than 1×10-3Pa, ion etching of the substrate surface is started. Argon gas is introduced at a flow rate of 350sccm. A pulse bias voltage of -850V, a frequency of 40kHz, a pulse width of 4μs, and an etching pressure of 1.1Pa is applied to the steel block sample. The steel block sample is pre-sputtered and cleaned for 20min using argon plasma.

[0040] (3) Deposition of Ti transition layer

[0041] High-power pulse magnetron sputtering technology was used, the argon flow rate was adjusted to 60sccm, the substrate bias was continuously adjusted to -200V, the frequency was 80kHz, and the pulse width was 6μs. A high-power pulse power supply was added to the pure Ti target, the peak current was adjusted to 180A, the frequency was 100Hz, the pulse width was 500μs, the average output power was 5kW, and a 90-100nm Ti transition layer was deposited for 15min.

[0042] (4) Deposition of TiN coating

[0043] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the argon flow rate was unchanged, nitrogen with a flow rate of 8 to 30 sccm was introduced, a pulse bias was applied to the steel block sample, the bias was -150 V, the frequency was 80 kHz, the pulse width was 6 μs, the deposition time was 10 min, and a TiN coating with a thickness of 70 to 80 nm was deposited.

[0044] (5) Deposition of TiCN coating

[0045] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept constant, the frequency was 100 Hz, the pulse width was 500 μs, the average output power was 5 kW, and the argon flow rate was kept constant at 60 sccm and the nitrogen flow rate was kept constant at 30 sccm. Acetylene was introduced, and the acetylene flow rate was continuously adjusted to 8-10 sccm. The bias voltage was adjusted to -120 V for deposition for 5 minutes. Then, the acetylene flow rate was kept at 10 sccm, the bias voltage was continuously adjusted to -90 V, the argon flow rate was adjusted to 60 sccm, and the deposition time was 7200 s to deposit the TiCN coating.

[0046] The elements and their atomic percentages in the TiCN composite coating prepared in Example 2 are N 20at.%, C 65at.%, and Ti 15at.%. The thickness of the TiCN composite coating is about 980nm, wherein the thickness of the bottom layer is 90-100nm, and the thickness of the middle layer is 70-80nm. A scratch test was performed using a multifunctional material surface performance tester (MFT-4000), which has a diamond Rockwell indenter with a cone angle of 120° HRC-3 and a tip radius of 0.2mm, and the end load is set to 90N, the scratch length is 5mm, and the loading speed is 50N / min. The scratch test is performed and the friction coefficient, friction force curve, and loading force curve are obtained. The scratch morphology of the coating is observed by an optical microscope (NMM-800) with a magnification of 100 times, and the comprehensive judgment of the bonding force of the coating is 65N. The coating was subjected to a reciprocating friction test using a CSM friction tester in an atmospheric environment using a 9Cr18 steel ball with a diameter of 6 mm. The measured average friction coefficient was approximately 0.29.

[0047] Example 3

[0048] A TiCN composite coating with high film-base bonding strength and low friction coefficient is prepared by high-power pulsed magnetron sputtering technology. The specific preparation steps are as follows:

[0049] (1) Pretreatment

[0050] The 9Cr18 alloy steel block substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 minutes respectively, and then placed in a drying chamber for standby use after being blown dry.

[0051] (2) Pre-sputtering cleaning

[0052] The 9Cr18 alloy steel block sample treated in step (1) is placed in a vacuum chamber for evacuation. When the vacuum degree is lower than 1×10-3Pa, ion etching of the substrate surface is started. Argon gas is introduced at a flow rate of 350sccm. A pulse bias voltage of -850V, a frequency of 40kHz, a pulse width of 4μs, and an etching pressure of 1.1Pa is applied to the steel block sample. The steel block sample is pre-sputtered and cleaned for 20min using argon plasma.

[0053] (3) Deposition of Ti transition layer

[0054] High-power pulse magnetron sputtering technology was used, the argon flow rate was adjusted to 60sccm, the substrate bias was continuously adjusted to -200V, the frequency was 80kHz, and the pulse width was 6μs. A high-power pulse power supply was added to the pure Ti target, the peak current was adjusted to 180A, the frequency was 100Hz, the pulse width was 500μs, the average output power was 5kW, and a Ti transition layer of 90-100nm was deposited for 15min.

[0055] (4) Deposition of TiN coating

[0056] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the argon flow rate was unchanged, nitrogen with a flow rate of 8 to 30 sccm was introduced, a pulse bias was applied to the steel block sample, the bias was -150 V, the frequency was 80 kHz, the pulse width was 6 μs, the deposition time was 10 min, and a TiN coating of 70 to 80 nm was deposited.

[0057] (5) Deposition of TiCN coating

[0058] High-power pulsed magnetron sputtering technology was used, the Ti target current was kept constant, the frequency was 100 Hz, the pulse width was 500 μs, the average output power was 5 kW, and the argon flow rate was kept constant at 60 sccm and the nitrogen flow rate was kept constant at 30 sccm. Acetylene was introduced, and the acetylene flow rate was continuously adjusted to 8-10 sccm. The bias voltage was adjusted to -120 V for deposition for 5 minutes. Then, the acetylene flow rate was kept at 10 sccm, the bias voltage was continuously adjusted to -90 V, the argon flow rate was adjusted to 90 sccm, and the deposition time was 7200 s.

[0059] The elements and their atomic percentages in the TiCN composite coating prepared in Example 3 are N 30at.%, C 40at.% and Ti 30at.%. The thickness of the TiCN composite coating is about 1030nm, including a bottom layer thickness of 90-100nm and an intermediate layer thickness of 70-80nm. A scratch test was performed using a multifunctional material surface performance tester (MFT-4000), which has a diamond Rockwell indenter with a cone angle of 120° HRC-3 and a tip radius of 0.2mm. The end load is set to 90N, the scratch length is 5mm, and the loading speed is 50N / min. The scratch test is performed and the friction coefficient, friction force curve, and loading force curve are obtained. The scratch morphology of the coating is observed using an optical microscope (NMM-800) with a magnification of 100 times, and the comprehensive judgment of the bonding force of the coating is 69N. The coating was subjected to a reciprocating friction test using a CSM friction tester in an atmospheric environment using a 9Cr18 steel ball with a diameter of 6 mm. The measured average friction coefficient was approximately 0.31.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. TiCN composite coating, characterized in that: It comprises three layers, a bottom layer is a Ti coating, a middle layer is a TiN coating, and a surface layer is a TiCN coating. The elements and their atomic percentages in the TiCN composite coating are N 20-30 at.%, Ti 15-30 at.%, and C 40-65 at.%.

2. The TiCN composite coating according to claim 1, characterized in that: The total thickness of the TiCN composite coating is 710-1030 nm, the thickness of the bottom layer is 90-100 nm, and the thickness of the middle layer is 70-80 nm.

3. The method for preparing the TiCN composite coating according to claim 1, characterized in that: A Ti transition layer, a TiN coating and a TiCN coating are sequentially deposited on the substrate surface by high-power pulsed magnetron sputtering technology.

4. The preparation method according to claim 3, characterized in that: The process conditions for depositing the Ti transition layer are as follows: argon flow rate 60sccm, substrate bias -200V, frequency 80kHz, pulse width 6μs, a high-power pulse power supply is added to the pure Ti target, the peak current is adjusted to 180A, the frequency is 100Hz, the pulse width is 500μs, the average output power is 5kW, and the deposition time is 15min.

5. The preparation method according to claim 3, characterized in that: The process conditions for depositing the TiN coating are as follows: Ti target peak current 180A, frequency 100Hz, pulse width 500μs, average output power 5kW, argon flow rate 60sccm, and nitrogen is introduced and the flow rate is continuously adjusted to 8~30sccm, bias voltage -150V~-180V, frequency 80kHz, pulse width 6μs, and deposition time 10min.

6. The preparation method according to claim 3, characterized in that: The process conditions for depositing the TiCN coating are as follows: Ti target peak current 180A, frequency 100Hz, pulse width 500μs, average output power 5kW, argon flow rate 60sccm, nitrogen flow rate 30sccm, bias voltage -120V, and gradually introducing 8-10sccm of acetylene. After 5min of deposition, the bias voltage is adjusted to -90V, the acetylene flow rate is maintained at 10sccm, the argon flow rate is adjusted to 30-90sccm, and the deposition time is 120min.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The substrate is pre-treated and pre-sputtered before the coating is deposited.

8. The preparation method according to claim 7, characterized in that: The pretreatment steps include: ultrasonic cleaning with anhydrous ethanol and petroleum ether for 30 minutes respectively, and placing in a drying chamber after drying.

9. The preparation method according to claim 8, characterized in that: The pre-sputtering cleaning step includes: placing the pre-treated substrate into a vacuum chamber for evacuation, with a vacuum degree of less than 1×10 -3 Pa, start ion etching on the substrate surface, introduce argon gas with a flow rate of 350sccm, apply a pulse bias on the substrate, the bias is -850V, the frequency is 40kHz, the pulse width is 4μs, the etching pressure is 1.1Pa, and pre-sputter clean the substrate with argon plasma for 20min.

10. The preparation method according to claim 9, characterized in that: The substrate is made of steel.